IMPMENTATION GENRE BASED APPROACH TO IMPROVE EXPLANATION TEXT WRITING SKILLS - Susetya, Hemas Haryas Harja; Hikam, Ahmad Ilzamul (Universitas Islam Zainul Hasan Genggong, 2024)
Writing is one of the productive skills in English, yet it is often considered difficult for students to master. One approach to improve writing skills is the Genre-Based Approach. This study aims to overcome students' writing difficulties by applying this approach. Classroom Action Research was chosen as the research model, in accordance with the identified problems. The study consisted of two cycles and focused on evaluating students' writing using a scoring rubric. The research subjects chosen for this study were VI grade students at MI SUNAN AMPEL II MARON. participated as research subjects. The pre-test and post-test served as instruments to collect students' writing products. In addition, data analysis was also supported by the results of the observation sheet. The results showed that students' weaknesses in writing were reduced after the implementation of the Genre-Based Approach. This was evidenced by more than 75% of students exceeding the minimum standard score. In addition, there was a noticeable improvement in students' writing ability in the post-test.